PMN Apoptosis Induced by SNHG11 through the Inhibition of Endotoxin-induced Acute Lung Injury NF-κB Pathway - Hu, Wenhui; Ying, Yaping; Jin, Lihong; Chen, Lingling; Zhou, Tingmin; Jin, Xiaohong (Cellular and Molecular Biology, 2022)
This study aimed to investigate the impacts of small nucleolar RNA host gene 11 (SNHG11) on nuclear factor kappa-B (NF-κB) pathway polymorphonuclear neutrophils (PMN) apoptosis in rats with endotoxin-induced acute lung injury (ALI). Forty rats were the experimental subjects. They were randomly grouped as a control group (Group C), an endotoxin group (Group E), an inhibitor group (Group I), and an activator group (Group A), with 10 rats in each group. The endotoxin-educed ALI rat model was built. Arterial Blood Gas Test (ABGT) was performed, and the Wet/Dry (W/D) ratio of lung weight was determined. The pathological variations in rat pulmonary tissues were scrutinized and scored. PMN in peripheral blood was isolated; its apoptosis was assessed, and its total NF-κB p65 and p-NF-κB p65 expressions were assessed. The expression of SNHG11 mRNA in pulmonary tissues was assessed. Results: Compared to Group C, the W/D ratios and pathological scores of Group E, Group I, and Group A boosted notably (P <0.05), while their ABGT indicators and PMN apoptosis rates dropped (P <0.05). Compared to Group E and Group I, the W/D ratio and pathological score of Group A dropped notably (P <0.05), while its ABGT indicators and PMN apoptosis rate boosted (P <0.05). Compared to Group C, the p-NF-κB p65 and SNHG11 expressions boosted in Group E, Group I, and Group A (P <0.05); compared to Group E and Group I, the p-NF-κB p65 and SNHG11 expressions in Group A dropped (P <0.05). SNHG11 could relieve endotoxin-induced ALI, which might be associated with the acceleration of PMN apoptosis and the inhibition of the NF-κB pathway.